Protagonists of War Spanish Army Commanders and the Revolt in the Low Countries - Fagel, Raymond (Leuven University Press, 2021)
Julián Romero, Sancho Dávila, Cristóbal de Mondragón, and Francisco de Valdés were prominent Spanish military commanders during the first decade of the Revolt in the Low Countries (1567-1577). Occupying key positions in this conflict, they featured as central characters in various war narratives and episodical descriptions of the events they were involved in, ranging from chronicles, poems, theatre plays, engravings, and songs to news pamphlets. To this day, they still figure as protagonists of historical novels: brave heroes in some, cruel oppressors in others. Yet personal, first-hand accounts also exist. Archival research into the letters written by these commanders now makes it possible to include their perspectives and the way they describe their own experiences. Looking through the eyes of four Spanish commanders, Protagonists of War provides the reader with an alternative reading of the Revolt, contrasting the subjective experiences of these protagonists with fictionalised perceptions.